Knowledge and perspectives in management of common childhood illnesses by caregivers to under-five children in southwestern nigeria: synopsis of self-medication practices - Oluseye Ademola Okunola; Mabayoje Anthony Olaniyi Aluko; Abdulrahman Azeez Aroke (Taylor & Francis Group, 2023)
AbstractThe information and opinions of the caregivers about various childhood ailments serve as a fundamental foundation for the practice of self-medication among under-five-year-old children. The outcome of the health status of children under five is greatly influenced by the scope of such knowledge and perception. The usage of medications for children is a major global problem since they are viewed as a vulnerable population. Although self-medication behaviors are widespread in Nigeria, little is known about how they affect the youngest, most vulnerable children. The knowledge and perceived management of common pediatric disorders among children under the age of five by their caregivers in southwest Nigeria were the subjects of this study. Based on their degree of cosmopolitanism and lack of cosmopolitanism, two local government areas from the states of Lagos and Osun were chosen for the study. Nine hundred and sixty-eight caregivers to under-five children were systematically randomly selected for the study. Data were collected with the aid of structured interviewer-administered questionnaire through the use of Open Data Kit. The knowledge and the perception of caregivers were assessed via vignette-designed questions that were explained to the respondents by the trained research assistants. The data were analyzed using the STATA Package software. The unit of analysis was frequency distribution and percentages. The common childhood illnesses identified by the respondents were malaria, otitis media (ear infection), gastro-enteritis (diarrheal and vomiting), measles, mumps, respiratory tract infection, and febrile convulsion. In general, the caregivers showed a very good knowledge of the CCI presented to them. They identified correctly the illnesses associated with the symptoms. In assessing the possible causes of these CCI, the caregivers commonly attributed the cause to natural phenomena like weather, seasonal changes, dust, and sunny environment. Also, poor hygienic conditions and infection by parasites were identified to be responsible for these CCI. However, their perceived causes of some CCI were very poor. The most visited source of procurement of medicaments was pharmacy or chemist shops in their locality. Pharmacists, friends, and parents were the sources of medication by adolescents as they procured over-the-counter drugs, analgesics, and antibiotics to self-medicate. The classes of products used mostly were drugs prescribed by doctors and any available medicine in their home. The predominant reason given by a greater proportion of the respondents is their affordability of the products which was represented by the cheap cost of self-medication practice in this study. In conclusion, the caregivers in this study are very knowledgeable on the various CCI affecting their under-five children and their belief in the probable causes of the CCI are tuned towards natural causes, infection by parasites, and environmental causes. It is believed that the degree of the caregiver's knowledge will determine the quality of childcare practice to their under-five children.